1996
DOI: 10.1002/(sici)1097-4547(19960201)43:3<289::aid-jnr4>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary neurotrophic factor selectively protects human oligodendrocytes from tumor necrosis factor-mediated injury

Abstract: Oligodendrocytes (OLs) and their myelin membranes are the apparent injury targets in the putative human autoimmune disease multiple sclerosis. The basis for this selective injury remains to be defined. OLs in vitro have been shown to be susceptible to both tumor necrosis factor (TNF) and non‐TNF‐dependent immune effector mechanisms. The former involves initial nuclear injury (apoptosis); the latter, when mediated by activated T cells, involves initial cell membrane injury (lysis). In the current study, we dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
1
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 49 publications
2
44
1
2
Order By: Relevance
“…In vitro CNTF promotes the survival of neurons 20,58 and reduces tumor necrosis factor-␣ and serum deprivationinduced cell death of oligodendrocytes. 19,59,60 In vivo, it prevents the degeneration of axotomized neurons. 23 In CNTF-deficient mice induction of EAE with MOG peptide results in more severe axonal damage, increased number of apoptotic oligodendrocytes, and a reduction in proliferating oligodendrocyte progenitor cells compared to WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro CNTF promotes the survival of neurons 20,58 and reduces tumor necrosis factor-␣ and serum deprivationinduced cell death of oligodendrocytes. 19,59,60 In vivo, it prevents the degeneration of axotomized neurons. 23 In CNTF-deficient mice induction of EAE with MOG peptide results in more severe axonal damage, increased number of apoptotic oligodendrocytes, and a reduction in proliferating oligodendrocyte progenitor cells compared to WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of inflammatory cytokines can be important in influencing CNS regeneration, either by direct neurotrophic actions, by causing astrocytes to become reactive, and /or by affecting the neurotrophic activity of astrocytes. It is possible that under certain conditions, inflammatory cytokines become impairments to the recovery of the CNS; for instance, TNF-␣ can be toxic to oligodendrocytes (Louis et al, 1993;D'Souza et al, 1996). Understanding and regulating the activities of inflammatory cytokines within the CNS constitutes a key step toward effecting CNS recovery.…”
Section: Table 2 Extent Of Astrogliosis In Cd1 Adult Mouse Brain Trementioning
confidence: 99%
“…15 and 41). A number of studies have observed that TNF-␣ produces apoptotic death to oligodendrocytes and neurons (19,21), and some reports have also implicated IL-1␤ in the mediation of neuronal death, particularly following ischemic and excitotoxic brain injury (42)(43)(44). Inflammation following CNS trauma would therefore be detrimental in the context of potential injury to neurons and oligodendrocytes, and reports of the correspondence of the number of macrophages/microglia with the amount of tissue damage at each level of the spinal cord in contusion injury (e.g., Carlson et al (45)) would be consistent with such a hypothesis.…”
Section: Figurementioning
confidence: 99%
“…18). CNTF has been shown to be an important maturation factor for oligodendrocytes, to promote their synthesis of myelin proteins (19,20), and to protect oligodendrocytes from apoptotic death induced by several agents (19,21). Thus, the regulation of CNTF expression in the CNS following injury may be particularly important for attenuating neuronal and oligodendrocyte death.…”
mentioning
confidence: 99%